Optimalisasi Pengembangan Desa Wisata Lerep Kabupaten Semarang Berbasis Kearifan Lokal - Landung Esariti; Rizqita Shofia Nida; Anita Ratnasari Rakhmatulloh; Sunarti Sunarti; Maya Damayanti; Okto Risdianto Manullang; Daniel Bayu Anggara (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Since 2015, Lerep has been appointed as a tourism village based on the Regent's Decree. The potential of local wisdom becomes the main attraction of the Lerep Tourism Village for developing tourism attraction. This article aims to provide an overview of the development of the Lerep Tourism Village by optimizing the existing potential and integration of community participation. The method used in this study is a descriptive qualitative approach by conducting in-depth interviews to key stakeholders. Data collection was conducted from April to July 2022 and interviews were conducted in June 2022. The number of respondents was 7 people who were representatives of tourism actors in the Lerep Tourism Village. The results of the analysis show that the Lerep Tourism Village has managed 7 types of tourist attractions which include natural tourism, educational tourism, water-based tourism, artificial tourism, culinary tourism, cultural tourism and homestays. This management involves active community participation by prioritizing the concept of local wisdom in 3 main aspects. First, there is an effort to highlight the unique natural potential that specifically exists in the Lerep Tourism Village in the form of natural beauty and the diversity of agricultural, fishery and plantation products. Second, encourage the participation of local communities via specific tourist attractions. Each community group is given the right to manage tourist attractions according to their respective expertise, for example in the fields of arts, culinary and tourism accommodation management. Third, the availability of a kinship-informal institutional model. This creates more effective communication between the key stakeholders of the Lerep Tourism Village.